Sero-prevalence of syphilis, risk factors and clinical characteristics among blood donors in a tertiary care hospital in Karachi, Pakistan - Samar, Rohama; Dodani , Sunil Kumar; Qureshi , Javeria; Moin , Hira; Badlani , Sanjay Kumar (Infectious Diseases Journal of Pakistan, 2025)
Background: Transfusion poses a risk of transfusion-transmitted infections. Our aim is to evaluate blood donors who test positive for syphilis in order to confirm the diagnosis, assess clinical features and establish risk factors. Material and Methods: A cross-sectional study was conducted from June to December 2024 at Sindh Institute of Urology and Transplantation (SIUT), Karachi. All blood donors who tested positive for treponemal antibodies by chemiluminescence immunoassay (TP-CMIA) were evaluated at the Infectious Diseases (ID) clinic between June to December 2024. History, examination and confirmatory testing with rapid plasma reagin (RPR) and Treponema pallidum hemagglutination (TPHA) tests were performed. Results: A total of 20,685 donors were screened, and 374 (1.8%) tested positive on TP-CMIA. Of 374, 152 (40.6%) presented to the clinic of whom 91 (60%) were confirmed to have syphilis. Of these, 61(40%) were RPR negative but TPHA positive. Mean age was 33.5 ± 7.93, and 150 (98.6%) were male. Pre-marital or extra-marital sexual relations were significantly associated with confirmed syphilis [OR 9.06, 95% CI (3.9-20.8)]. Conclusion: Sero-prevalence of syphilis in blood donors is 1.8% at our centre. It is of concern that 40 % of donors with confirmed syphilis were negative for RPR, as this is used for initial screening at many blood donation centres. Pre-marital and extra-marital high-risk sexual activities were highly associated with confirmed syphilis. A thorough and detailed history can effectively identify and exclude high-risk donors for blood donation, providing a cost-effective approach to screening. Keywords: Syphilis, Screening, Blood donors